Impact of methods of estimating baseline Serum Creatinine (bSCr) on the incidence and outcomes of acute kidney injury in childhood severe malaria - Olayinka Rasheed Ibrahim; Folake Moriliat Afolayan; Michael Abel Alao; Bashir Mohammed; Bello Mohammed Suleiman; Olanrewaju Timothy Adedoyin (SpringerOpen, 2023)
Abstract Background Estimated baseline serum creatinine (bSCr) affects the incidence and outcomes of childhood severe malaria. Herein, we estimated baseline serum creatinine (bSCr) levels of 541 children with severe malaria using Pottel and Scwartz formulas for AKI incidence, hospitalization outcomes, and evaluated risk factors for death. Methods This was a retrospective review of malaria cases from January 2019 to December 2020 at a tertiary health facility in northern Nigeria. We extracted relevant data from the electronic health record. AKI definition and staging was based on the 2012 Kidney Disease Improving Global Outcomes (KDIGO). Results The estimated bSCr using Pottel's method was lower with a mean (standard deviation) bias of -0.039 (0.013) mg/dl, an upper limit of agreement (-0.014 mg/dl), and the lower limit of agreement (-0.063 mg/dl). All (100%) of the estimated bSCr using Pottel's method fell within 30% of the Schwartz method's estimated bSCr. The incidence of AKI from Pottel's method was higher than the Schwartz's method (43.3% vs. 38.4%, p < 0.001). The incidence of AKI derived from Pottel's method was highest among those under 5 years old (p < 0.001). The mortality rate was 6.1% (33 deaths out of 541 admissions). Pottel's method detected more deaths (57.6%; 19 out of 33) vs. Schwartz's method (48.5%; 16 out of 33), p < 0.001. Factors that were associated with malaria AKI death included acidosis with an adjusted odds ratio (AOR) of 9.2 (95% CI 1.671 to 50.097), the first 72 h [AOR 7.0 (95% CI 1.358, 35.840)], and KDIGO stage 3 of AKI [AOR 14.4 (95% CI 3.073, 66.969)]. Conclusion Among Nigerian children with severe malaria, bSCr back-calculated from Pottel's equation showed a minimal bias, narrow limit of agreement, and high degree of accuracy. Also, Pottel's method detected more AKI and deaths.